Author Correction: Lineage tracing of acute myeloid leukemia reveals the impact of hypomethylating agents on chemoresistance selection - Francisco Caiado (Nature Portfolio, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.